2017
DOI: 10.1002/cncr.30606
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 study of immunotherapy with dendritic cells pulsed with autologous tumor lysate in patients with refractory bone and soft tissue sarcoma

Abstract: Although DC therapy appears safe and resulted in an immunological response in patients with refractory sarcoma, it resulted in an improvement of the clinical outcome in only a small number of patients. Cancer 2017;123:1576-1584. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…21 22 Mifamurtide, a liposome-encapsulated immunotherapy that activates pulmonary macrophages, improved the disease-free and overall survival of patients with osteosarcoma lung metastases. 23 By contrast, MoDC vaccines have yielded little to no clinical responsiveness, [24][25][26] while checkpoint blockade with PD-1 or CTLA-4 antibodies led to objective clinical response rates of approximately 5% in osteosarcoma patients. 27 28 These results underscore the critical need to improve therapeutic options for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…21 22 Mifamurtide, a liposome-encapsulated immunotherapy that activates pulmonary macrophages, improved the disease-free and overall survival of patients with osteosarcoma lung metastases. 23 By contrast, MoDC vaccines have yielded little to no clinical responsiveness, [24][25][26] while checkpoint blockade with PD-1 or CTLA-4 antibodies led to objective clinical response rates of approximately 5% in osteosarcoma patients. 27 28 These results underscore the critical need to improve therapeutic options for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…DC vaccines have produced delays in disease progression and even the regression of established osteosarcomas in animal models . However, only limited activity was seen in the two clinical trials using DC vaccines pulsed with autologous tumor cell lysate in patients with recurrent osteosarcoma . These studies did, however, show that this strategy is safe and can activate the immune system to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical efficacy of DC‐based immunotherapy demonstrated by Miwa et al was modest. Future clinical studies of immunotherapy augmented by bacterial therapy may provide much better outcomes, and it should be evaluated in clinical trials in the near future.…”
mentioning
confidence: 97%
“…OK‐432 is a preparation from Streptococcus pyogenes that has been reported to be immunomodulatory . In the study by Miwa et al, increased levels of serum interferon‐γ and interleukin 12 were seen after DC‐based immunotherapy, and this indicated that DC‐based immunotherapy activated the immune responses of the patients. No adverse effects associated with the DC‐based immunotherapy were observed in the study patients.…”
mentioning
confidence: 98%
See 1 more Smart Citation